Using panicle dry weight to estimate seed production in Echinochloa crus‐galli. (6th September 2019) - Pannwitt, H; Westerman, P R; De Mol, F; Gerowitt, B
Summary: A better understanding of weed seed production is a key element for any long‐term management allowing some weeds to shed seeds. The challenge with measuring seed production in weeds is the large effort required in terms of time and labour. For the weed species Echinochloa crus‐galli, it was tested whether the number of seeds per panicle dry weight or per panicle length can be used to estimate seed production. Experiments were conducted in three maize fields in north‐eastern Germany. The effect of factors that could influence this relationship, such as the time of seedling emergence, the density of E. crus‐galli, the control intensity of other weeds, seed predation and field, was included. A few days before maize harvest, all panicles were removed and weighed, panicle length was measured, and for a subsample of 178 panicles, the number of seeds was counted manually. Panicle dry weight predicted the number of seeds per panicle better ( R 2  = 0.92) than did panicle length ( R 2  = 0.69). The other factors except for 'field' and 'seed predation' had no effect on these relationships. The relationships between seed number and panicle dry weight found in this study closely resembled those reported in an earlier study. Based on our results, we conclude that both plant traits are appropriate for the estimatation of seed production, depending on required level of precision and availablilty of resources for the evaluation of sustainable weed management strategies.